P13: CHARACTERISATION OF THE TUMOUR MICROENVIRONMENT IN MESENCHYMAL GASTRIC TUMOURS USING SINGLE-CELL RNA SEQUENCING. (27th April 2021) - Harrington, J; Lloyd, M; Mabrouk, N; Walker, R; Grace, B; Underwood, T
Abstract: Introduction: Gastric mesenchymal tumours are a rare group of neoplasms, which include gastrointestinal stromal tumours (GISTs) and leiomyomas. To date, there is limited information on the tumour microenvironment (TME) in these neoplasms, despite the TME widely known to influence the hallmarks of cancer. In this study we used single cell RNA sequencing (scRNAseq) to profile individual cells of the TME in GIST and leiomyoma. Method: The two gastric mesenchymal tumours and two normal gastric samples were analysed using DropSeq, where single cell transcriptomes are captured onto barcoded beads using a microfluidic device before next generation sequencing. For comparison, we performed bulk RNA-sequencing and CIBERSORT to estimate the abundance of 22 immune cell populations. Furthermore, we used immunohistochemistry to elucidate the presence and location of several immune cells. Result: Both neoplasms had diverse immune and stromal cell populations with a greater proportion of macrophages but less B cells than normal gastric tissue. ScRNAseq was able to identify subpopulations of B cells and T cells not detected with CIBERSORT. Interstitial cells of cajal, believed to be the pre-cursor to GISTs, were observed through scRNAseq and confirmed through immunohistochemistry. Conclusion: To our knowledge, this is the first study to utilise scRNAseq on GISTs and leiomyomas, which enabled characterisation of the TME at a cellular level. Using this platform in future studies will enable better characterisation of the TME and may inform the discovery of therapeutic targets. Take-home message: Single cell RNA sequencing enables the ability to explore the tumour microenvironment of mesenchymal tumours at an enhanced resolution, paving the way for potential future therapeutic targets.